2005
DOI: 10.1038/sj.bmt.1704997
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism for low yield of blood culture in invasive aspergillosis; the clinical importance of antigen detection tests revisited

Abstract: The mechanism for low yield of blood culture in invasive aspergillosis; the clinical importance of antigen detection tests revisited Bone Marrow Transplantation (2005) 36, 85-86.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Genome ontology enrichment analysis showed significant overrepresentation of complement cascade (5-fold enrichment, p < 1.55 X 10 −2 ). Consistent with the lack of circulating organisms in patients with acute IPA [ 10 ], no high confidence protein matches were obtained by searching peptide fingerprints within multiple Aspergillus databases ( Materials and Methods ). From these data we concluded that complement and coagulation cascades were components of the host response to IPA, and that active post-translational modification of these proteins were produced, perhaps through their consumption or proteolysis as a consequence of angio-invasion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome ontology enrichment analysis showed significant overrepresentation of complement cascade (5-fold enrichment, p < 1.55 X 10 −2 ). Consistent with the lack of circulating organisms in patients with acute IPA [ 10 ], no high confidence protein matches were obtained by searching peptide fingerprints within multiple Aspergillus databases ( Materials and Methods ). From these data we concluded that complement and coagulation cascades were components of the host response to IPA, and that active post-translational modification of these proteins were produced, perhaps through their consumption or proteolysis as a consequence of angio-invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, diagnosis of IPA is established on the basis of radiographic, culture, and fungal antigen detection in high-risk patients [ 6 , 9 ]. Despite hematogenous dissemination, fungal blood cultures are rarely positive [ 10 ]. The development of fungal antigen assays has added to the available diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional diagnostic methods for BSIs require several days to complete, and both false positive [15,16] and false negative results [17,18] have been reported. Delayed diagnosis correlates strongly with the high mortality of BSIs [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, human aspergillosis typically starts as an infection of the respiratory tract. Culturing of Aspergillus from the blood of aspergillosis patients is usually not successful, hinting at a limited systemic component of the disease (26).…”
mentioning
confidence: 99%